PROFIL KECERDASAN MAJEMUK (MULTIPEL INTELEGENSI) PESERTA DIDIK SMAN 12 PADANG - Fiera Kurniati; Mori Dianto; Rici Kardo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the diversity of student potential at SMA N 12 Padang, which has not been optimally mapped. Although the school has attempted to implement modern educational concepts, the learning process often remains conventional and tends to emphasize specific cognitive abilities, such as linguistic and logical-mathematical. In reality, every individual possesses uniqueness through multiple intelligences. The purpose of this study is to describe the multiple intelligences profiles of student at SMA N 12 Padang, specifically focusing on linguistic, visual-spatial, bodily-kinesthetic, intrapersonal, and interpersonal intelligences. This study employs a descriptive quantitative research method, invoving students of class X Phase E as the subjects. The data collection instrument used is a multiple intelligences profile questionnaire. The results of this study are expected to seve as a reference for guidance and counseling teachers as well as subject teachers in mapping student potential, furthermore, these findings are intended to provide a basis for determining differentiated learning strategies to enhance students’ motivation and academic achievement. The results of this study reveal that: 1) it can serve as a reference for guidance and counseling teachers as well as subject teachers in mapping student potential, and as a basis for determining differentiated learning strategies to enhance students’ motivation and academic achievement